2010
DOI: 10.1103/physrevb.82.094106
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of defect cluster and the stability of xenon in uranium dioxide from density functional calculations

Abstract: Self-defect clusters in bulk matrix might affect the thermodynamic behavior of fission gases in nuclear fuel such as uranium dioxide. With first-principles local spin-density approximation plus U calculations and taking xenon as a prototype, we find that the influence of oxygen defect clusters on the thermodynamics of gas atoms is prominent, which increases the solution energy of xenon by a magnitude of 0.5 eV, about 43% of the energy difference between the two lowest lying states at 700 K. Calculation also re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 34 publications
1
61
0
Order By: Relevance
“…Due to its high impact on nuclear fuel performance the properties of Xe in UO 2±x have been extensively studied using a variety of theoretical 2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and experimental techniques [3][4][5][25][26][27][28][29][30][31] . Matzke et al [3][4][5] have published several reviews on this topic and concluded that Xe diffusion can be represented by an Arrhenius model, D = D 0 e −Ea/k b T , with activation energies (E a ) that depend on UO 2±x stoichiometry.…”
Section: Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its high impact on nuclear fuel performance the properties of Xe in UO 2±x have been extensively studied using a variety of theoretical 2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and experimental techniques [3][4][5][25][26][27][28][29][30][31] . Matzke et al [3][4][5] have published several reviews on this topic and concluded that Xe diffusion can be represented by an Arrhenius model, D = D 0 e −Ea/k b T , with activation energies (E a ) that depend on UO 2±x stoichiometry.…”
Section: Thermodynamicsmentioning
confidence: 99%
“…A related model was introduced by Geng et al in the UO 2+x regime 24 . In principle, our study could be expanded to include such effects but this exercise has been left as future work and our discussion refers to the thermodynamic model in Table I.…”
Section: Thermodynamicsmentioning
confidence: 99%
“…[7]. Especially, in order to eliminate electronic meta-stable states that introduced via strong correlations of 5f orbitals, we adopted the quasi-annealing method [8] to lower the electronic energy slowly by controlling the random disturbance from the ionic system which acts as a kind of heat bath. Defect populations were evaluated using point defect model [9][10][11] and presumed a physical condition in the closed regime, which corresponds to the interior of a bulk material and thus no exchange of particles with the exterior can occur.…”
mentioning
confidence: 99%
“…Where possible, comparison has also been made to literature UO 2 DFT results [14,44,45,46]. Figure 4 shows similar trends for the trapping energies for Xe and Kr defects in CeO 2 , ThO 2 , UO 2 and PuO 2 between the empirical potential and the DFT methods used in this paper.…”
Section: Validation Of Empirical Parametersmentioning
confidence: 65%
“…DFT results (partially filled columns) are reported from the literature [14,44,45,46] and the present study (using Table 2) for comparison with the new empirical potential potential (solid columns).…”
Section: Gas--ion Separation (å)mentioning
confidence: 99%